Penerapan Model Pembelajaran Problem Based Learning Dalam Meningkatkan Hasil Belajar IPA Kelas IV MI Sirojul Athfal Depok - Annas Al Fiani; Sri Wuryastuti (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2022)
The research that was conducted departed from a learning problem in Natural Sciences for fourth grade students of MI Sirojul Athfal Depok where most of the students scored still below the KKM. In the learning process activities carried out in the classroom the teacher still uses the lecture and question and answer method, so that students are less actively involved in the learning process. The purpose of this study is to improve the quality of the teaching and learning process in the classroom and improve student learning outcomes by applying the problem based learning model. The research was in the form of Classroom Action Research (CAR) which was conducted during the second cycle of the research. Each cycle has four stages, namely planning, implementation, observation, and reflection. The research subjects were fourth grade students of MI Sirojul Athfal which consisted of 24 students, 13 male students and 11 female students. Collecting data using test techniques to measure student understanding, observation, documentation, and field notes. The results of the research application of the problem based learning model were obtained in the first cycle as many as 15 students (62.5%) students could achieve the KKM while in the second cycle there was an increase of 21 students (87.5%) students could reach the KKM. In addition to student learning outcomes, the activities of teachers and students also increased as seen from the activity of each observation in each cycle and the learning process carried out in class was much better.